Facilitated Oxygen Chemisorption in Heteroatom‐Doped Carbon for Improved Oxygen Reaction Activity in All‐Solid‐State Zinc–Air Batteries. Issue 4 (6th December 2017) - Liu, Sisi; Wang, Mengfan; Sun, Xinyi; Xu, Na; Liu, Jie; Wang, Yuzhou; Qian, Tao; Yan, Chenglin
Abstract: Driven by the intensified demand for energy storage systems with high‐power density and safety, all‐solid‐state zinc–air batteries have drawn extensive attention. However, the electrocatalyst active sites and the underlying mechanisms occurring in zinc–air batteries remain confusing due to the lack of in situ analytical techniques. In this work, the in situ observations, including X‐ray diffraction and Raman spectroscopy, of a heteroatom‐doped carbon air cathode are reported, in which the chemisorption of oxygen molecules and oxygen‐containing intermediates on the carbon material can be facilitated by the electron deficiency caused by heteroatom doping, thus improving the oxygen reaction activity for zinc–air batteries. As expected, solid‐state zinc–air batteries equipped with such air cathodes exhibit superior reversibility and durability. This work thus provides a profound understanding of the reaction principles of heteroatom‐doped carbon materials in zinc–air batteries. Abstract : Facilitated chemisorption of oxygen molecules and oxygen‐containing intermediates on the heteroatom‐doped carbon is observed by in situ characterization during the zinc–air battery operation. Improved oxygen reaction activity is induced by this process as confirmed by experimental results. This work gives a new protocol for the operating principle investigation of energy storage systems.